2007
DOI: 10.3171/spi-07/12/656
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival enhanced by cordectomy in a patient with a spinal glioblastoma multiforme and paraplegia

Abstract: ✓Spinal glioblastomas multiforme (GBMs) are rare lesions of the central nervous system with a prognosis as poor as that of their intracranial counterpart. The authors present a case of a 50-year-old man with a GBM of the spinal cord treated with surgical removal of the mass and cordectomy after the onset of paraplegia. Six years later, the patient developed hepatitis C and received interferon therapy. Six months after the start of interferon therapy, magnetic resonance imaging revealed a right cerebell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…In fact, to our knowledge, the literature contains only 7 reported cases in which cordectomy was used to treat spinal cord tumors, 1,7,9,14,15,21,25 none of which involved pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, to our knowledge, the literature contains only 7 reported cases in which cordectomy was used to treat spinal cord tumors, 1,7,9,14,15,21,25 none of which involved pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…In 2005, Raza et al 21 reported performing cordectomy in a 65-year-old patient with a recurrent atypical meningioma of the thoracic spine, although they were unable to achieve a total resection due to persistent meningeal involvement. Marchan et al 15 performed cordectomy for a spinal GBM in a 50-year-old man. Approximately 3 months after establishing the diagnosis of spinal GBM and after the patient had become progressively paraplegic despite radiotherapy and chemotherapy, Marchan and colleagues opted to undertake a spinal cordectomy rather than debulk the lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An initial strategy of biopsy may be more appropriate than attempted resection for a patient with suspected radiation-induced spinal astrocytoma. 7) Cordectomy is advocated as a reasonable alternative treatment for spinal malignant astrocytoma presenting with complete deficit below the lesion, 6,9,12) for the treatment of pain, spasticity, and posttraumatic syringomyelia. 10,20,22) The effects of cordectomy for spinal malignant astrocytoma with remaining function below the lesion are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Rare long-term survivors have been seen with 'radiocordectomy', in which radiation above the tolerance of the spinal cord is administered at the tumour bed, although this should be reserved for patients who are already paraplegic. The two reported cases of patients who received this treatment survived for 6 and 12 years respectively [7,14].…”
Section: Accepted Manuscript -4 -mentioning
confidence: 99%